Investigating life skills among young students in Malaysia - Mofrad, Sakineh *; Chee, Kwan Foong *; Koh, Andrea Emmanuel; Ikechukwu, Uba (IACSIT Press, 2013)
The study examined the life-skills perception of freshmen undergraduate students. The respondents of the survey were 500 young adults aged 18 to 25 years from selected universities in Subang Jaya, Malaysia. Life-skills Development Inventory-College Form was used to measure life skills in four domains: interpersonal communication, decision making, health maintenance and identity development. The finding revealed significant gender difference in health maintenance. Recommendations of the study underscored the relevance of the findings in interventions and skills building activities.